After the Covid-19 Pandemic: Rethinking the Relationship between Technology and Teacher Training - Maria Grazia Simone (International Journal of Education, 2024)
The paper proposes a reflection on the new development trajectories of teacher training in light of the impact with the Covid-19 pandemic. The health emergency is producing, among other aspects, a rethinking of the relationship between those who teach and new technologies. The hypothesis to be demonstrated is that the current experience is configured as an important opportunity for professional growth for the teacher if this profession becomes increasingly open to the demands of the present time, ready to respond to emergencies that may arise in teaching practice, skilled in managing and mastering a conscious and mature relationship with technology. The paper also presents the partial results of a research, carried out in three Italian universities, on the relationship between teachers in the training phase and technologies in this pandemic time.